Diretrizes para a sustentabilidade de uma minirrede de sistemas solares fotovoltaicos em uma região isolada da Colômbia - Manrique, Ana Katherine Rodríguez (2015)
This research presents the development of a social-technical study to define guidelines to ensure the sustainability of a mini-grid based on solar photovoltaic systems located in Non Interconnected Areas (NIA) of Colombia. The literature of this research is based on the importance of energy and sustainable buildings to people, the principles of solar PV, and mini-grid based on solar photovoltaic systems. After this firt part, was applied the method of documentary research to contextualize the reader with the main relevant aspects of Colombia related to the research. From these aspects, it was possible to focus the research to a region, which was chosen by criterias such as: solar resource, economy, security, health and education. When the area was chosen, it was made a field survey. In this survey the agents that influence the operation of a mini network were interviwed. Also, it was observed the technical aspects of buildings, and the energy efficiency in this region. As a result it was observed that in the past there were PV solar systems, but these were sold by the community because they did not find them useful. From the interview answers, it was made a proposal about the management of the mini-grid based on solar photovoltaic systems. In conclusion, it is essential that the technical and administrative agents that make part of this system have continuous contact with the user to understand their needs and satisfy them with the installation of mini-grid. It is also important to create a sense of belonging from the user to the mini-grid, identifying the benefits, educational, health and economic that this new technology brings to him. This study opens the door to new research about evaluations and descriptions about the proposed guidelines.